A new species of Heterachthes Newman, 1840 from Colombia (Coleoptera, Cerambycidae) - Santos-Silva, Antonio; Botero, Juan Pablo (Zootaxa, 2017)
Heterachthes was originally created by Newman (1840) for a single species from the United States of America (Florida): H. ebenus Newman, 1840. Currently, Heterachthes encompasses 68 species distributed to southern USA to southern South America (Monné 2016; Tavakilian and Chevillotte 2016). Of these species, six occur in Colombia: H. concretus, Martins, 1970; H. ebenus; H. lateralis Martins, 1962; H. sablensis Blatchley, 1920; H. signaticollis (Thomson, 1865); and H. vauriae Martins, 1971.